A Testament of Devotion and Thomas Kelly, Augustinian Quaker - Aiken, Guy, (Brill Research Perspectives in Humanities and Social Sciences., 2021)
Guy Aiken provides a critical appreciation of Quaker mystic Thomas Kelly (1893-1941) and his classic A Testament of Devotion (1941). This examination of Kelly's life and devotional writings is largely viewed through an Augustinian lens; Augustine's Confessions was a touchstone for Kelly after his mystical transformation in 1937-38. Aiken argues that Kelly's vision of Quakerism transcended religious and historical boundaries, while still speaking directly, and prophetically, to mid-twentieth-century liberal Quakerism and Christianity in the United States. The volume treats, in turn, Kelly's melding of liberal and evangelical theology, his prophetic call to his contemporaries, and his revival of an ancient ethic, before concluding with helpful suggestions for further research.